Thermal entanglement in the three-qubit Tavis-Cummings model with Kerr nonlinearity - Bagrov, A.R.; Bashkirov, E.K. (Kompʹûternaâ optika, 2025)
We obtained a solution of the Liouville equation for a system of three identical qubits interacting without detuning with a thermal field of a cavity with a Kerr medium, for two type of initial pure genuine W-entangled qubits states. On its basis, three entanglement parameters: fidelity, tangle and pairwise negativities were calculated. We obtained that sudden death of entanglement takes place for large intensities of the cavity thermal noise for all considered W-states. We also showed that Kerr nonlinearity prevents the destruction of the initial qubits entanglement induced by the thermal noise of the cavity and eliminates the sudden death of entanglement.